1999
DOI: 10.1103/physrevb.60.13573
|View full text |Cite
|
Sign up to set email alerts
|

Substitutional carbon inSi1xGex

Abstract: Local vibrational modes of carbon impurities in relaxed Si 1Ϫx Ge x have been studied with infrared absorption spectroscopy in the composition range 0.05рxр0.50. Carbon modes with frequencies in the range 512-600 cm Ϫ1 are observed in 13 C ϩ -implanted Si 1Ϫx Ge x after annealing at 550°C. Measurements on samples coimplanted with 12 C ϩ and 13 C ϩ show that these modes originate from defects containing a single carbon atom and from the variation of the mode frequencies with composition x, the modes are assigne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
10
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 18 publications
(29 reference statements)
2
10
0
Order By: Relevance
“…A preferential pairing between a substitutional B atom and a substitutional Ge atom rendering the B atom partly immobile has been put forward to explain the retardation. 19 Hoffmann et al 20 have demonstrated by infrared absorption experiments that a substitutional carbon atom in strain relaxed Si 1Ϫx Ge x of xр0.50 prefers a configuration with four Si neighbors. Thus, for C i a pairing with Ge atoms is excluded.…”
mentioning
confidence: 99%
“…A preferential pairing between a substitutional B atom and a substitutional Ge atom rendering the B atom partly immobile has been put forward to explain the retardation. 19 Hoffmann et al 20 have demonstrated by infrared absorption experiments that a substitutional carbon atom in strain relaxed Si 1Ϫx Ge x of xр0.50 prefers a configuration with four Si neighbors. Thus, for C i a pairing with Ge atoms is excluded.…”
mentioning
confidence: 99%
“…Several groups have reported on Raman spectroscopy studies of Si 1−x Ge x :C. [9][10][11][12] Two Raman peaks, one at 607 cm −1 and the other at 560 cm −1 , have been identified as carbon LVMs in Si 1−x−y Ge x C y 11) and their frequencies depends only on the Ge composition x when y 0.01, and on both x and y when y 0.01. 12) The microscopic origin of the two peaks at 607 cm −1 and 560 −1 have been revealed by IR absorption studies performed by Hoffmann et al 1,7,8) In this paper we report on Raman investigations of 13 C LVM in * E-mail address: kitoh@appi.keio.ac.jp Si 1−x Ge x :C samples.…”
mentioning
confidence: 73%
“…It is possible to estimate the positions of Peak 1 and 2 theoretically using the following assumptions. 1) The positions of Peak 1 and 2 depend only on the composition x of Ge and not on the composition y of C, because the concentration of carbon is very low in our samples (y ≈ 0.002 for our Si 1−x−y Ge x C y ). Peak 1 and 2 are formed predominantly by the T 2 mode of Si 4 Ge 0 -C and the A 1 mode of Si 3 Ge 1 -C, respectively, i.e., the peak positions of Peak 1 and 2 can be estimated simply by calculating the frequencies of the T 2 mode of Si 4 Ge 0 -C and the A 1 mode of Si 3 Ge 1 -C, respectively, as a function of the Ge composition x.…”
mentioning
confidence: 75%
See 2 more Smart Citations